Incident and Risk factors of Low Birth Weight Infants in Teenage Pregnancy in Sing Buri Hospital - Chaisrisookumporm, Niran (Journal of Health Science of Thailand, 2017)
Teenage pregnancy have a higher risk of complications more than adults. Teenage period of females is the transitional stage of physical and mental development. Most complication is low birth weight, the important health problems of Thailand, leading to morbidity and mortality of infants. The objective of this retrospective analytic study was to determine the incidence and risk factors of low birth weight in teenage pregnancy in Sing Buri Hospital. Data was collected from medical records of all teenage pregnants delivered in Sing Buri Hospital during 2 year period between January 1,2009 and December 31,2010. Statistical analysis of antenatal history, mode of delivery and birth weight were carried out. There were 479 teenage pregnants accounting for 200 per 1000 delivered. The average age was 17.5 year. Most of them were graduated from secondary schools (76.3%), reported as housewives (76.3%) and had vaginal delivery (83.7%). There were 57 low birth weigh infants accounting for 119 per 1000 newborns. Risk factors of low birth weight included poor antenatal care less than 4 times (p < 0.05) (odds ratio 9.78, 95% CI 1.11, 18.58), gestational age less than 37 weeks (p < 0.05) (odds ratio 18.16, 95% CI 11.15, 25.15), hematocrit less than 30% (p < 0.05) (odds ratio 6.42, 95% CI 2.62, 10.22) and maternal weight gain less than 10 kilograms (p < 0.05) (odds ratio 3.68, 95% CI 2.70, 4.57). The encouraging of adequate antenatal care and motivate teenage pregnants to take care of nutritional habits will lead to good health for both mothers and infants.